1997
DOI: 10.1136/hrt.78.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of ventricular repolarisation: a marker of ventricular arrhythmias in patients with previous myocardial infarction

Abstract: Objective-To examine whether, in coronary patients after myocardial infarction, the dispersion of ventricular repolarisation measured through QT and JT intervals from a surface electrocardiogram could allow separation of those with ventricular tachyarrhythmias (VT) complicating their myocardial infarct from those without. Design-A retrospective comparative study. Setting-University hospital. Patients-39 patients with myocardial infarction complicated by VT, 300 patients after myocardial infarction without arrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 21 publications
1
28
1
2
Order By: Relevance
“…It is exhibited in patients with myocardial infarction, subarachnoid hemorrhage and diabetes mellitus. 5,6,[17][18][19][20] In the present study, however, no arrhythmic events were observed during laparoscopic cholecystectomy in both elderly and younger patients. This may be due to the fact that patients with cardiac diseases were not included in this study.…”
Section: Me Et Th Ho Od Ds Scontrasting
confidence: 39%
“…It is exhibited in patients with myocardial infarction, subarachnoid hemorrhage and diabetes mellitus. 5,6,[17][18][19][20] In the present study, however, no arrhythmic events were observed during laparoscopic cholecystectomy in both elderly and younger patients. This may be due to the fact that patients with cardiac diseases were not included in this study.…”
Section: Me Et Th Ho Od Ds Scontrasting
confidence: 39%
“…The sympatho-vagal imbalance and the prolonged QT dispersion are considered to be a marker of electrical instability and risk factors for ventricular arrhythmias (3)(4)(5). The absence of any clinically important arrhythmias on the 24-h ECG monitoring of our patients suggests that other factors (triggers) could be required for the development of sustained or life-threatening ventricular arrhythmia.…”
Section: Discussionmentioning
confidence: 97%
“…Low magnitude repolarization gradients during steady pacing increase significantly with extrastimuli by virtue of delayed activation to sites in proximity to the origin of pacing. These gradients may in turn provide the substrate for functional conduction block and reentrant arrhythmias (15,23,27). By extrapolation, critically timed spontaneous PVCs arising in the RV may also create similar proarrhythmic substrate, and further trigger reentry.…”
Section: Discussionmentioning
confidence: 99%